ANALISIS KORELASI KARAKTER MORFOLOGI TANAMAN KARET (Hevea brasiliensis (Willd. ex A. Juss) Mull. Arg.) DENGAN PRODUKTIVITASNYA DARI LIMA SENTRA PRODUKSI KARET PROPINSI RIAU - M. Adi Zulkifli; Fitmawati '; Dewi Indriyani Roslim (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Rubber plant (Hevea brasiliensis (Willd. ex A. Juss) Mull. Arg.) is one ofcommercial commodities in Riau Province that distributed at several plantation centerssuch as Bengkalis Regency, Kampar, Kuantan Singingi, Meranti, and Rokan Hulu. Thepropagation of rubber plants in long period of time causes variety in latex production.Nowdays, most of the rubber plantations in Riau Province use unstandardized seedlingthat result in diverse and low latex production. The first way to increate latex productionis to identify the morphological characters related to latex production. This research wasaimed to find out the characters that had correlation with latex productivity level. Thisresearch used exploration method. Samples such branches, leaves, and seeds from 10rubber trees for each regency were collected, hence there were 50 samples wereanalyzed. The sample collection was based on the production level. A total of 66morphological characters were analyzed. Seven out of 66 observed character had acorrelation with latex production i.e. dense branch of tree, dense leaf of tree, dense leafof branch, length petiole of main leaf, length petiole of leaflet, length of leaf, and wideof lamina. These characters can be used to select superior rubber plant.